Laporan pelaksanaan tahunan Proyek Peningkatan Peranan Wanita Tani-Nelayan Prop. Sulawesi Selatan tahun 1982/1983 (Departemen Pertanian, Kantor Wilayah Prop. Sulawesi Selatan, 1983)
Implementation of project to increase income of the fishermen by improving the knowledge, skill, and ability of the women in supporting their family; research report in Sulawesi Selatan Province; only issue available.